Dopamine and Glutamate in Antipsychotic-Responsive Compared With Antipsychotic-Nonresponsive Psychosis: A Multicenter Positron Emission Tomography and Magnetic Resonance Spectroscopy Study (STRATA). (10th September 2020) - Egerton, Alice; Murphy, Anna; Donocik, Jacek; Anton, Adriana; Barker, Gareth J; Collier, Tracy; Deakin, Bill; Drake, Richard; Eliasson, Emma; Emsley, Richard; Gregory, Catherine J; Griffiths, Kira; et al.
Abstract: The variability in the response to antipsychotic medication in schizophrenia may reflect between-patient differences in neurobiology. Recent cross-sectional neuroimaging studies suggest that a poorer therapeutic response is associated with relatively normal striatal dopamine synthesis capacity but elevated anterior cingulate cortex (ACC) glutamate levels. We sought to test whether these measures can differentiate patients with psychosis who are antipsychotic responsive from those who are antipsychotic nonresponsive in a multicenter cross-sectional study. 1 H-magnetic resonance spectroscopy ( 1 H-MRS) was used to measure glutamate levels (Glucorr ) in the ACC and in the right striatum in 92 patients across 4 sites (48 responders [R] and 44 nonresponders [NR]). In 54 patients at 2 sites (25 R and 29 NR), we additionally acquired 3, 4-dihydroxy-6-[18F]fluoro-l -phenylalanine ( 18 F-DOPA) positron emission tomography (PET) to index striatal dopamine function ( K i cer, min −1 ). The mean ACC Glucorr was higher in the NR than the R group after adjustment for age and sex ( F 1, 80 = 4.27; P = .04). This was associated with an area under the curve for the group discrimination of 0.59. There were no group differences in striatal dopamine function or striatal Glucorr . The results provide partial further support for a role of ACC glutamate, but not striatal dopamine synthesis, in determining the nature of the response to antipsychotic medication. The low discriminative accuracy might be improved in groups with greater clinical separation or increased in future studies that focus on the antipsychotic response at an earlier stage of the disorder and integrate other candidate predictive biomarkers. Greater harmonization of multicenter PET and 1 H-MRS may also improve sensitivity.